Effect of mulch and biofertilizers on forage and seed yield of italian ryegrass (Zoo Botanica, 2025)
In semi-arid regions, Italian ryegrass (Lolium multiflorum) serves as a crucial forage crop with its productivity reduced because of deficient soil water resources and poor nutrient conditions. The sustainable production of forage seeds along with plant seeds depends heavily on resolving these key issues in resource-limited areas. This research evaluated the synergistic impacts between using mulch with biofertilizers on Italian ryegrass soil conditions and vegetation growth and seed and forage yield development. Researchers conducted a two-year outdoor trial (2023-2025) in the research facilities of PMAS Arid Agriculture University Research Farm Rawalpindi through Randomized Complete Block Design (RCBD) while working with three duplicate units. The research implemented seven treatments that included Control as T1 and combination treatments as T2 through T7 which were Mulch, Bio-fertilizer, Fertilizer, Mulch + Fertilizer, Mulch + Bio-fertilizer, Mulch + Fertilizer + Bio-fertilizer. Standard methods allowed researchers to measure both the soil properties such as moisture, mineral nitrogen, extractable potassium, and available phosphorus and agronomic parameters like plant height, tillers, biomass, grain yield, crude protein, fixed protein in the studied area. The researchers used ANOVA together with LSD and correlation analysis for their statistical evaluations. The combination of Mulch and Fertilizer endowed with Bio-fertilizer (T7) created significant soil moisture increase by 17.33% and raised mineral nitrogen levels by 52.50 mg/kg and extractable potassium by 259.17 mg/kg and available phosphorus by 102.50 mg/kg above control levels (P < 0.0001). Total plant height reached 5.83 cm and the maximum tillers per plant numbered 6.33 in treatment T7 which also resulted in the best fresh biomass output at 5688.8 kg/ha and highest dry matter yield at 1427.3 kg/m² and final grain yield of 17.57 g/m². The percentage of crude protein rose to 1.80%, but the crude fiber content lowered to 5.00% which shows enhanced forage quality. High and positive relationships (r > 0.96) were detected between water content, nutrient availability, yield measurement variables, yet crude fiber exhibited negative correlations (r = -0.94). Research findings show that combining mulch with bio-fertilizers through T7 application method leads to outstanding improvements in Italian rye grass soil health and plant expansion, resulting in superior forage and seed production yields. The authors underline integrated nutrient management as a promising approach for enhancing productivity and forage quality, specifically in semi-arid regions among farmers who operate with constrained resources.
Keywords: Biofertilizers; forage crop; italian ryegrass; livestock